Aktualni problemi pri inventarizaciji gradiva v luči zbiranja statističnih podatkov - Poličnik-Čermelj, Tereza (Knjižnica, 2010)
Accession is the process of recording bibliographic units in an accession register. Typically, library materials are acquired by purchase, exchange, gift or legal deposit. However, COBISS (Cooperative Online Bibliographic System and Services) Holdings software module includes some additional methods of acquisition which causes problems in gathering and presenting statistical data on local holdings. The article explains how to record holdings of different types of library materials and how to record retrospective collections. It describes necessary procedures in case the codes that define the publication pattern of the holdings are changed with special attention to integrating resources. Procedures of accession and circulation of bound materials, supplementary materials, teaching sets, multi parts, multimedia and collection level catalogue records and described. The attention is given to errors in recording lost item replacements and to the problems of circulation of certain types of library materials. The author also suggests how to record remote electronic resources. It is recommended to verify holdings data before the accession register is generated. The relevant and credible statistical data on collection development can only be created by librarians with sufficient acquisition and cataloguing skills.
Keywords: inventarizacija; statistika; izposoja gradiva; COBISS Zaloga